2001
DOI: 10.1080/0158791010220107
|View full text |Cite
|
Sign up to set email alerts
|

International distance education: Cultural and ethical issues

Abstract: This paper describes an international online program run by the University of British Columbia (UBC) in Canada in association with Monterrey Institute of Technology in Mexico. It highlights the problems of online collaboration and assessment criteria for students from different cultures and pedagogical heritages. It also raises a range of issues faced by the initiating university (UBC) in developing and presenting a global online course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 1 publication
2
23
0
2
Order By: Relevance
“…These results revealed that Taiwan has a better infrastructure for technology than India for providing online learning. Our results are consistent with the studies that indicated that culture and language play an influential role in online learning environment (Barak et al, 2016;Bates, 2001;Gunawardena et al, 2001;Mercer, 2000). The results of this study are also consistent with the study by Lim (2004) that highlight importance of cross-cultural settings in online learning.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results revealed that Taiwan has a better infrastructure for technology than India for providing online learning. Our results are consistent with the studies that indicated that culture and language play an influential role in online learning environment (Barak et al, 2016;Bates, 2001;Gunawardena et al, 2001;Mercer, 2000). The results of this study are also consistent with the study by Lim (2004) that highlight importance of cross-cultural settings in online learning.…”
Section: Discussionsupporting
confidence: 83%
“…They found that culture influences participant's online learning behavior in terms of collectivism and context communication. Bates (2001) also concluded that culture differences influence the online teaching-learning process in terms of students' willingness to participate in the online discussion forum. Some researchers found that cultural differences create barriers in students' communication and social-interaction which affect learner's overall learning performance, motivation, and satisfaction in online learning (Hamdan, 2014;Kerr, 2014;Olaniran, 2009;Uzuner, 2009).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Within the context of a globalizing world economy, CUAED will enable Latin-American countries to develop their own capacity for developing distance education programming (.e.g., Spanish contents will be available for Latin America's Spanish speaking population) to meet the growing educational needs of their people. This reinforces the statement by Bates (2001) who said: "help must be provided in a way that reduces rather than increases dependency, by enabling local institutions to develop their own capacity for online teaching adapted to the needs of their own society. "…”
Section: Delegationsupporting
confidence: 60%
“…Οι δύο μεταβλητές του μοντέλου αυτού είναι η αντιληπτή χρησιμότητα και η αντιληπτή ευκολία χρήσης (Halawi & McCarthy, 2008;Ngai, Poon & Chan, 2007;Johnson, Hornik & Salas, 2008). Τέλος, μία ακόμα σημαντική παράμετρος η οποία σχετίζεται με την παρούσα έρευνα είναι η ετοιμότητα στη χρήση της γλώσσας επικοινωνίας (Mason & Gunawardena, 2001;Bates, 2001;Goodfellow, Lea, Gonzalez & Mason, 2001;Zhang & Kenny, 2010). Εκτός από τις παραπάνω παραμέτρους που εξ αρχής κρίθηκε σκόπιμο να διερευνηθούν, στην πορεία της παρούσας έρευνας ως σημαντικές αναδείχθηκαν δύο ακόμη παράμετροι: α) η ενεργητική συμμετοχή των εκπαιδευομένων στις διάφορες δραστηριότητες και β) τα στοιχεία της προσωπικότητάς τους και οι ατομικές στρατηγικές μάθησης που εφαρμόζουν.…”
Section: εισαγωγήunclassified